2012
DOI: 10.3390/molecules17066362
|View full text |Cite
|
Sign up to set email alerts
|

4-Thiazolidinones in Heterocyclic Synthesis: Synthesis of Novel Enaminones, Azolopyrimidines and 2-Arylimino-5-arylidene-4-thiazolidinones

Abstract: The 4-thiazolidinones 3a–d were used as a key intermediates for the synthesis of 2-arylimino-5-arylidene-4-thiazolidinones derivatives 7a–p via nucleophilic addition reactions with the arylidene malononitrile. Moreover the 4-thiazolidinones 3a and 3c condensed with the DMF-DMA to form the corresponding enamines 8 and 9 depending on the reaction conditions. Otherwise the 4-thiazolidinone 3b reacts regioselectively with DMF-DMA to afford the enaminones 10 and 11, respectively. The latter reacts with many heteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Moreover conducting the reaction between the methyl-2-(2-chloroaceta-mido) benzoate ( 3 ) and the ammonium thiocyanate in absolute methanol afford two products depending on the refluxing time, 4 was formed after 6h while the methyl-2-[(4-oxo-3,4-dihydroquinazolin-2-yl)thio]acetate ( 5 ) was formed after 12 h and not compound 6 or 7 [43,44]. Also compound 5 can be obtained by refluxing the formed methyl-2-(2-thiocyanatoacetamido)benzoate ( 4 ) in methanol [45] (cf.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover conducting the reaction between the methyl-2-(2-chloroaceta-mido) benzoate ( 3 ) and the ammonium thiocyanate in absolute methanol afford two products depending on the refluxing time, 4 was formed after 6h while the methyl-2-[(4-oxo-3,4-dihydroquinazolin-2-yl)thio]acetate ( 5 ) was formed after 12 h and not compound 6 or 7 [43,44]. Also compound 5 can be obtained by refluxing the formed methyl-2-(2-thiocyanatoacetamido)benzoate ( 4 ) in methanol [45] (cf.…”
Section: Resultsmentioning
confidence: 99%
“…However, after detailed literature survey it was observed that there were only limited publications devoted to the synthesis of especially thiazolo[3,2- a ]quinazoline which involved reaction of 2-mercaptopropargyl quinazolin-4-one with various aryl iodides catalyzed by Pd-Cu [39] or by condensation of 2-mercapto-4-oxoquinazoline with chloroacetic acid [40], inspite of this procedure was also reported in the literature to afford the thiazolo[2,3- b ]quinazoline. So the multistep synthesis of thiazoloquinazolines especially thiazolo[3,2- a ]quinazoline suffered from some flaws and in continuation of our research program on the synthesis of nitrogen and sulphur containing novel heterocycles [41-43] of pharmaceutical interest and in view of the operational simplicity in this study we have synthesized a novel class of thiazoloquinazolines by a simple and convenient method involving catalysis by DABCO. The X-ray single crystal technique as an advanced tool of analysis was employed in this study for structure elucidation and for determination the regioselectivety of the reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The product formed was recrystallized in ethanol (1-15). These compounds have already been reported in the following literature [24][25][26][27][28][29][30][31][32] For aliphatic (2-Chloro-acetamides): To a stirring solution of amine in 10 ml dichloromethane, triethylamine was added.…”
Section: General Procedures For the Preparation Of Different Substitutmentioning
confidence: 99%
“…The 4-thiazolidinone ring system is a core structure in various synthetic compounds and an important scaffold known to be associated with several biological activities such as hypnotic activity, antitubercular, anticonvulsant, antibacterial, anticancer, antihistaminic, antifungal, anti-inflammatory, antiviral, and cardiovascular effects [174]. Generally, these heterocycles are synthesized easily by a three-component condensation of a primary amine, an aldehyde, and a mercaptoacetic acid.…”
Section: Thiazoles and Thiazolidinonesmentioning
confidence: 99%